2009
DOI: 10.1029/2008jb005763
|View full text |Cite
|
Sign up to set email alerts
|

Progressive strain localization in a major strike‐slip fault exhumed from midseismogenic depths: Structural observations from the Salzach‐Ennstal‐Mariazell‐Puchberg fault system, Austria

Abstract: [1] Analysis of a strike-slip fault exhumed from midseismogenic depths reveals that the fault experienced progressive strain localization toward a high-strain fault core. We focus on the Ennstal segment of the 400-km-long Salzach-Ennstal-Mariazell-Puchberg (SEMP) strike-slip fault system in the Eastern Alps, which accommodated $60 km of left lateral displacement during Oligo-Miocene time. Macroscopic and microscopic observations reveal a zoned fault featuring a high-strain core at least 10 m wide within a faul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 54 publications
6
29
0
Order By: Relevance
“…For large faults in northern California, the damage zone width inferred from Table 7 is 120 ± 40 m, in line with geologic estimates from large exhumed strike‐slip faults [ Chester et al , 2004; Frost et al , 2009], faults exposed in mines [ Wallace and Morris , 1986], and studies of fault zone trapped waves elsewhere [ Ben‐Zion et al , 2003; Lewis et al , 2005]. The narrow damage zone is consistent with a simple fault geometry comprising a single fault core bounded on one or both sides by a variably fractured material (Figure 18a), similar to exposures of the San Gabriel, San Andreas, and San Jacinto faults [ Chester et al , 2004; Dor et al , 2006].…”
Section: Rough Fault Loading Modelsupporting
confidence: 82%
“…For large faults in northern California, the damage zone width inferred from Table 7 is 120 ± 40 m, in line with geologic estimates from large exhumed strike‐slip faults [ Chester et al , 2004; Frost et al , 2009], faults exposed in mines [ Wallace and Morris , 1986], and studies of fault zone trapped waves elsewhere [ Ben‐Zion et al , 2003; Lewis et al , 2005]. The narrow damage zone is consistent with a simple fault geometry comprising a single fault core bounded on one or both sides by a variably fractured material (Figure 18a), similar to exposures of the San Gabriel, San Andreas, and San Jacinto faults [ Chester et al , 2004; Dor et al , 2006].…”
Section: Rough Fault Loading Modelsupporting
confidence: 82%
“…Geochronological data from these cataclastic shear zones are rare (e.g., Wölfler et al 2010). Although the existing reconstructions indicate that the main part of orogen-parallel extension occurred during Early to Middle Miocene times (Frisch et al 2000), seismic events along most of these faults indicate that these are still active (e.g., Reinecker and Lenhardt 1999;Reinecker 2000;Lenhardt et al 2007;Frost et al 2009) and that a certain amount of displacement has been accommodated until recent times.…”
Section: Introductionmentioning
confidence: 99%
“…Fault zone localization within competent rock was also observed at the Punchbowl fault in California, in which the protoliths are primarily arkosic sandstone and igneous basement rock [Chester and Chester, 1998] and can be considered analogous to the localized deformation we observe in lithified Berea sandstone. Frost et al [2009] observed strain localization within a wide fault core in the Salzach-EnnstalMariazell-Puchberg (SEMP) fault in Austria. This wide fault zone is formed in carbonate rocks (dolomite and limestone) and is consistent with the wide deformation zones we observe in lithified limestone and marble.…”
Section: Implications For Slip Behavior In Natural Fault Systemsmentioning
confidence: 99%